Safe bites on the streets: an analysis of food safety and hygiene among Shah Alam's street food vendors / Muhammad ‘Arif Aizat Bashir ... [et al.] - Bashir, Muhammad ‘Arif Aizat; Zaihan, Sarah; Salim, Shahrool Rezza; Osman, Mohamed Syazwan; Siregar, Juliana (Universiti Teknologi MARA, Terengganu, 2024)
Lack of personal hygiene among food handlers and inadequate cleaning practices during food service operations have led to numerous outbreaks of foodborne illness cases in Malaysia. Therefore, the purpose of this study was to investigate the influence of knowledge and attitudes on food safety and hygiene practices among street food vendors in Shah Alam, Malaysia. A sample of 376 street food vendors was surveyed using a structured questionnaire to gather information about their knowledge, attitudes, and food safety and hygiene practices. The study found a significant positive relationship between knowledge and attitudes towards food safety and hygiene practices, indicating the importance of maintaining educational programs for street food vendors to enhance their knowledge and attitudes. This study highlights the importance of addressing the knowledge and attitudes of street food vendors as a crucial step in improving food safety and hygiene in the food service industry. Moreover, the study recommends the implementation of food safety regulations and regular monitoring of street food vendors to ensure the safety of street food for the public. In conclusion, this study sheds light on the critical role of knowledge and attitudes in shaping food safety and hygiene practices among street food vendors. It highlights the need for ongoing education and training programs, as well as the implementation of regulations and monitoring mechanisms, to ensure the safety of street food consumed by the public. The results of this study are important for policymakers and food safety authorities in their efforts to improve food safety and hygiene in the food service industry.